Investigating the efficacy of medium pressure UV and hydrogen peroxide as on-farm treatment methods to reduce the microbial load of irrigation water - Kotze, Madelize J. (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc Food Sc)--Stellenbosch University, 2015.